Easy Is Not Always Good – The Fragmented System for Adjudication of Unitary Trade Marks and Designs - Annette Kur (IIC - International Review of Intellectual Property and Competition Law, 2021)
While the creation and still outstanding implementation of the Unified Patent Jurisdiction system continue to cause contentious debates among academics and practitioners, the system introduced in the early 1990s for adjudication of conflicts concerning unitary trade marks (and, later on, unitary design rights) had the charm of simplicity. Building on the national court systems instead of providing for a genuine EU judiciary, the scheme could easily be fitted into existing structures. On the other hand, the imperfect, limping character of the system creates issues inter alia concerning international jurisdiction and applicable law. Furthermore, attributing jurisdiction in infringement litigation to separate national court hierarchies may jeopardize the coherence of the system. While the prospects for reform may be dim insofar as the system in its entirety is concerned, the detrimental effects of fragmentation could be overcome at least to some extent by creating a unitary catalogue of sanctions.
Keywords: 340; EU trade mark law; EU design law; International jurisdiction; Applicable law; Sanctions for infringement